Infant and Young Child Feeding (draft resolution proposed by the delegations of Algeria, Bangladesh, Belgium, Democratic Yemen, Denmark, Finland, France, Gambia, Ghana, Iceland, India, Kenya, Lesotho, Mali, Mozambique, Netherlands, New Zealand, Norway, Pakistan, Romania, Samoa, Somalia, Sri Lanka, Swaziland, Sweden, Switzerland, Tonga, Trinidad and Tobago, Uganda, United Kingdom of Great Britain and Northern Ireland, United Republic of Tanzania, United States of America, and Yugoslavia) - World Health Assembly, 33 (World Health Organization, 1980)
(Agenda item 23)